2007
DOI: 10.1002/sia.2593
|View full text |Cite
|
Sign up to set email alerts
|

Identification of segregation phase on a batch hot‐dip‐coated Zn/0.1Al/0.2Sb surface

Abstract: The segregation of antimony in a batch hot-dipped regular-spangle galvanized coating from a Zn-0.1Al-0.2Sb bath was investigated. The samples were characterized by using SEM/EDS. The nature of the segregation phase was determined by XRD as bSb 3 Zn 4 . Assisted with Sb-Zn phase diagram, the behavior of antimony during the solidification process of the Zn-0.1Al-0.2Sb coating is examined. It is suggested that the coating solidification proceeds in three stages. Owing to the cooling rate of batch hot dip galvaniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…Moreover, the studies have shown that the addition of Sb can improve the fluidity of the bath and reduce the surface tension. In addition, the addition of Sb at a small content (0.04-0.2 wt.%) can improve the uniformity of the zinc coating and the bonding force with the steel substrate [15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the studies have shown that the addition of Sb can improve the fluidity of the bath and reduce the surface tension. In addition, the addition of Sb at a small content (0.04-0.2 wt.%) can improve the uniformity of the zinc coating and the bonding force with the steel substrate [15][16].…”
Section: Introductionmentioning
confidence: 99%